Consumption Behavior of Economics Education Students Faculty of Economics, State University of Manado - Allen A. Ch. Manongko; Henry J.D. Tamboto; Sophia Pongoh; Sjeddie Rianne Watung (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
This study aims to determine the influence of financial literacy and social environmental factors on consumption behaviour of Economics Faculty of Economics students of Manado State University. The design of this study using the quantitative approach with survey method, with the number of samples is 67 students as respondents through proportionate stratified random sampling. The research instrument used questionnaire with a Likert scale which then tested the validity and reliability. Data analysis techniques include 1) Descriptive analysis; 2) Classical assumption test, and 3) Multiple linear regression analysis. The results showed: 1). There is a significant influence on financial literacy and student consumption behaviour, with the influence of financial literacy on student consumption behaviour of 54.4%; 2). There is a significant influence on social environment factor with student consumption behaviour, with the influence of social environment factor to student consumption behaviour equal to 37.5%; and 3). There is the influence of variable of financial literacy and social environment factor to student consumption behaviour variable with a contribution equal to 78.6%. Conclusion, partially or simultaneously financial literacy and social environmental factors have a significant effect on the consumption behaviour of students of Economics Education Faculty of Economics, State University of Manado.